Colorectal cancer (CRC) as a multifactorial disease and its causal correlations with multiple signaling pathways. Issue 3 (20th March 2020) - Wan, Mao-lin; Wang, Yu; Zeng, Zhi; Deng, Bo; Zhu, Bi-sheng; Cao, Ting; Li, Yu-kun; Xiao, Jiao; Han, Qi; Wu, Qing
Abstract: Colorectal cancer (CRC) is the third most common malignancy and one of the leading causes of cancer-related death among men worldwide. CRC is a multifactor digestive pathology, which is a huge problem faced not only by clinicians but also by researchers. Importantly, a unique feature of CRC is the dysregulation of molecular signaling pathways. To date, a series of reviews have indicated that different signaling pathways are disordered and have potential as therapeutic targets in CRC. Nevertheless, an overview of the function and interaction of multiple signaling pathways in CRC is needed. Therefore, we summarized the pathways, biological functions and important interactions involved in CRC. First, we investigated the involvement of signaling pathways, including Wnt, PI3K/Akt, Hedgehog, ErbB, RHOA, Notch, BMP, Hippo, AMPK, NF-κB, MAPK and JNK. Subsequently, we discussed the biological function of these pathways in pathophysiological aspects of CRC, such as proliferation, apoptosis and metastasis. Finally, we summarized important interactions among these pathways in CRC. We believe that the interaction of these pathways could provide new strategies for the treatment of CRC.